Economic Impacts of Agricultural, Food, and Natural Resource Industries in Florida in 2004 - Alan W. Hodges; Mohammad Rahmani; W. David Mulkey (EDIS)
FE680, a 15-page illustrated report by Alan W. Hodges, Mohammad Rahmani, and W. David Mulkey, aims to quantify the magnitude of contributions agricultural, food and natural resource industries make to the economy of Florida in 2004. This report updates a previous study for 2003. Includes references, glossary of economic impact terms, and tables including economic impacts by industry sector, by value added and employment by region, fastest growing sectors, and value added and employment by industry groups. Published by the UF Department of Food and Resource Economics, December 2006.